2019
DOI: 10.1177/0300060519887267
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral holmium laser resection and transurethral electrocision combined with intravesical epirubicin within 24 hours postoperatively for treatment of bladder cancer

Abstract: Objective: To investigate the efficacy and safety of transurethral holmium laser resection (THOLR) and transurethral electrocision (TUR) combined with intravesical epirubicin within 24 hours postoperatively for treatment of non-muscular invasive bladder cancer. Methods: A total of 218 consecutive patients who were newly diagnosed with bladder cancer were enrolled in this prospective study from July 2014 to December 2017. The patients were randomly divided into THOLR and TUR groups. All patients received intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…11 In 24-month progression rates, Lu et al reported 9.2% (10/109) for ERBT and 10% (11/109) for cTURBT. 15 In 36-month progression rates, Zhang et al reported 5.4% (8/149) for ERBT and 7.0% (10/143) for cTURBT. 40 On the other hand, Chen et al reported no progression in both treatment arms during the 18-month followup.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…11 In 24-month progression rates, Lu et al reported 9.2% (10/109) for ERBT and 10% (11/109) for cTURBT. 15 In 36-month progression rates, Zhang et al reported 5.4% (8/149) for ERBT and 7.0% (10/143) for cTURBT. 40 On the other hand, Chen et al reported no progression in both treatment arms during the 18-month followup.…”
Section: Resultsmentioning
confidence: 98%
“…According to our inclusion criteria, we finally identified 29 studies comprising 4,484 patients for meta-analysis. 9–16,24,25,29,36–50,51–53 Of 29 included studies, 13 RCTs comprising 1,792 patients were eligible for analysis of oncologic and perioperative outcomes, 9–16,36–40 and 5 RCTs and 16 NRCTs/observational studies comprising 3,369 patients were eligible for analysis of pathological and reTUR outcomes. 10–13,24,25,29,40–50,51–53 The demographics of each included study are represented in tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations